Ketogenic dietary therapies in epilepsy: recommendations of the Italian League against Epilepsy Dietary Therapy Study Group - De Giorgis, Valentina; Tagliabue, Anna; Bisulli, Francesca; Brambilla, Ilaria; Camerini, Alessandra; Cusmai, Raffaella; Darra, Francesca; Dianin, Alice; Domenica, Elia; Lodi, Monica Anna Maria; Matricardi, Sara; Messana, Tullio; et al. (Frontiers in Neurology, 2023)
A stepwise increase in Ketogenic dietary therapies utilization for drug resistant epilepsy has been seen in Italy in the last decade, although it is still lately considered and often underused in many centers as compared to other Countries. The Diet- Therapy Study Group of the Italian League against Epilepsy proposes practical recommendations to improve shared knowledge and facilitate the application of Ketogenic dietary therapies, optimizing their efficacy and tolerability. The experts involved (eleven child neuropsychiatrists, two adult neurologists, one psychologist, one pharmacologist, one pediatric endocrinologist, one representative of patients’ associations and three dietitians and clinical nutritionists) responded to a survey on current clinical practice issues and were asked to discuss on controversial topics related to supplementation, long term maintenance, transition and multidisciplinary approach to KDT. Practical indications for patient selection, diet initiation, management, side effects prevention and follow-up are provided.